GENESIS OF THE CONCEPT OF PEDAGOGICAL TECHNOLOGY - A. M. Shekhmirzova (Science and Innovation Center Publishing House, 2020)
The article examines the issue of the history of the emergence of pedagogical technology as a concept and direction of pedagogical science. The essence of pedagogical technology is revealed, starting from the time of Y.A. Comenius to the present day. The evolutionary development of generic concepts to the term pedagogical technology is shown.